The Effect of Pine Oil Emulsifier on Gasoline-Alcohol Blends in a Spark Ignition Engine with Multi-Point Fuel Injection - Kavati, Venkateswarlu; Kavati, Veladri; Krishna Varma, Kola Poornodaya Venkata (Trends in Sciences, 2022)
This paper presents the results of a study conducted to establish the effect of pine oil as an emulsifier on gasoline-alcohol blends in a twin cylinder spark ignition (SI) engine with multi-point fuel injection (MPFI) system. The test fuels were prepared by blending both ethanol and isopropanol with gasoline separately and pine oil was used as an emulsifier to either of the fuel blends. The 3 sets of fuel samples were used in which the concentration of pine oil was kept constant at 20 % by volume, while the concentration of both alcohols namely ethanol and isopropanol was varied from 5 to 15 % and the rest is gasoline. The experiments were conducted at different loads from 0 to 100 % in steps of 20 % at a constant speed of 2500 rpm. The results demonstrate that the use of gasoline-alcohol blends with pine oil in MPFI SI engine improved brake thermal efficiency (BTE) by 7.8 and 11.2 % with the higher proportions of ethanol and isopropanol in gasoline, i.e., E15 and IPA15, respectively when compared to neat gasoline. Carbon monoxide (CO) and hydrocarbon (HC) emissions reduce by 22.5 and 27.5 %, respectively while HC emissions reduce by 21.5 and 28.8 %, respectively with the E15 and IPA15, respectively. However, higher amounts of nitrogen oxides (NOx) emissions is the negative impact of the said blends. It was also observed that there is a reduction in brake specific fuel consumption (BSFC).